Glaciological and geophysical investigations aimed at organization of a new airfield at the Station Mirny (East Antarctica) - S. V. Popov; S. V. Mezhonov; S. P. Polyakov; V. L. Mart'yanov; V. V. Lukin (Лëд и снег)
Main results of glaciological and geophysical engineering surveys, conducted during three summer field seasons of 2013– 2016 (59–61st Russian Antarctic Expeditions  – RAE) near the Russian Station Mirny (East Antarctica), are discussed in the paper. Objective of these works was to site and then to organize a new airfield for landing of medium-range aircrafts with ski landing gears. Investigations included aerial photography, GPR surveys (georadar profiling), ice core drilling, and installation of landmarks to measure velocity of the glacier motion. The GSSI ground-penetrating radars with the main frequencies of 270 MHz and 900 MHz were used. In addition, special explorations were conducted for detecting the englacial crevasses by means of remote-sensing methods. The GPR data allowed a revealing the boundary between snow-andfirn thickness and atmospheric ice. In the course of processing of 252 travel-time curves of the diffracted waves a kinematic model of the sub-surface part of the glacier has been constructed. It was found that the dielectric permittivity of the snowfirn thickness averages 2.43; similar value for the atmospheric ice amounts to 3.0. The GPR data made it possible to determine intraglacial (englacial) crevasses and to choose the most favorable field for the landing. On February 10, 2016, the first middle-range aircraft DC-3T (BT-67) had landed onto the new run-way near the station Mirny.